Penerapan Sistem Evaluasi Kinerja Bagi Guru Di Madrasah Ibtidaiyah (MI) Al Hayah - Dinda Wulandari; Asep Surya Lesmana; Aep Saefullah; Tetty Nur Intan Rifia; Ika Fatmasari; Eka Dea Safitri; Laela Punky Azzahra; M.Tafsiruddin (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to examine the implementation of performance evaluation system for teachers in Madrasah Ibtidaiyah (MI) Al-Hayah. Teacher performance evaluation is important in improving the quality of education and the effectiveness of learning in madrasah. This study used qualitative research methods with a case study approach. The research participants included 20 teachers of MI Al-Hayah, by collecting data through in-depth interviews, classroom observations, and document analysis related to performance evaluation. The results show that the implementation of the performance evaluation system at MI Al-Hayah still faces several challenges, such as a lack of understanding of the purpose of the evaluation, lack of management support, and limited resources. The results show that the implementation of an effective performance evaluation system provides significant benefits for teachers and administrative personnel at MI Al-Qur'an Al-Hayah. This performance evaluation system provides a clear picture of the quality of individual performance, identifies strengths and weaknesses, and provides constructive feedback for professional development. In addition, the system also contributes to increased motivation and work accountability.